2021
DOI: 10.1021/acs.iecr.0c04861
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Extractions from NaCl Brines to Pseudoprotic Ionic Liquids

Abstract: In liquid–liquid extractions, the aqueous phase from which heavy metal ions are extracted often contains a mixture of salt ions (brine). These additional salt ions may have an effect on the efficiency and selectivity of the extraction of a specific heavy metal ion and may cause a shift in extraction mechanism when the organic phase is an ionic liquid. This has been demonstrated in this study for the extraction of Co, Ni, or Zn chloride by three pseudoprotic ionic liquids (PPILs) in the absence or presence of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Later on, Davis and co-workers introduced the concept of tailored-made functionalized ionic liquids or task-specific ionic liquids (TSILs), where they made receptors an intrinsic part of ionic liquids for specific functions. Since then, the TSILs have attracted the notice of many researchers around the globe for various applications. Furthermore, Rogers and co-workers have demonstrated that binary mixtures of TSILs and less expensive hydrophobic ILs can be used as the extracting phase . Though ionic liquids are well explored as a better partitioning media for extraction studies, relatively less explored for sensing studies but rarely explored for dual functional studies. , Though these early reports were impressive, but the fluorescence sensing studies were carried out in a nonaqueous medium using hydrophobic TSILs, which do not represent a true sensory system. However, a proper sensory probe should be water-soluble.…”
Section: Introductionmentioning
confidence: 99%
“…Later on, Davis and co-workers introduced the concept of tailored-made functionalized ionic liquids or task-specific ionic liquids (TSILs), where they made receptors an intrinsic part of ionic liquids for specific functions. Since then, the TSILs have attracted the notice of many researchers around the globe for various applications. Furthermore, Rogers and co-workers have demonstrated that binary mixtures of TSILs and less expensive hydrophobic ILs can be used as the extracting phase . Though ionic liquids are well explored as a better partitioning media for extraction studies, relatively less explored for sensing studies but rarely explored for dual functional studies. , Though these early reports were impressive, but the fluorescence sensing studies were carried out in a nonaqueous medium using hydrophobic TSILs, which do not represent a true sensory system. However, a proper sensory probe should be water-soluble.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the IL-DLLME technique is mainly applied to the extraction of biological samples, such as saliva [35], blood [36], urine [37], and food analysis; for example, it is used in the separation of polychlorinated biphenyls (PCBs) and acrylamide from milk and coffee samples [38]. ILs as extractants are also widely used in the hydrometallurgical industry; examples include extracting alkali metals [39,40], alkaline earth metals [41], heavy metals [42][43][44], and transition metals [45]. Plastic is ubiquitous in our lives and poses a clear danger to organisms when released into the environment as a waste product; this represents one of the most pressing ecological issues at present [46][47][48].…”
Section: Introductionmentioning
confidence: 99%
“…These challenges motivate advances in harnessing alternate resources that cogenerate other high-value products alongside H 2 with reduced environmental impacts compared to conventional H 2 production technologies. Unlocking the use of natural brines (as in the case of seawater) or produced brines resulting from processes, such as desalination, can potentially limit (a) CO 2 emissions compared to existing processes, (b) the need for freshwater supply, and (c) the release of brines into water bodies, which can be harmful to marine life . Motivated by these challenges, this study aims to develop brine electrolysis approaches for coproducing H 2 along with other high-value products .…”
Section: Introductionmentioning
confidence: 99%